Attitudes of Iraqi society towards the role of community pharmacists - Abdulrasoul Wayyes; Haydar F. Al Tukmagi; Inas R. Ibrahim (University of Minnesota Libraries Publishing, 2013)
Objectives: The main aims of this study were to assess society's use of community pharmacies; evaluate attitudes towards the role of the community pharmacist; and describe required pharmacist characteristics and future services.Study design: A cross-sectional survey with a stratified sampling technique.Methods: A self-administered, validated, questionnaire was distributed to 500 consumers in attendance at 50 community pharmacies in Baghdad, Iraq. Data were gathered from January to April 2012. Mann-Whitney and Kruskal-Wallis tests were performed to test for statistical differences among the study variables. Further analysis through the Chi-square test and logistic regression was completed to assess the predictors of society's attitudes.Results: Twenty-six percent of respondents visited their community pharmacies at least once per week and an additional 65% reported visiting their pharmacy at least once per month. Fifty-five percent of respondents listed the community pharmacist as the first person they would contact in case of any drug-related problem. However, the pharmacist's role was under-appreciated by the majority of respondents (79.8%). These attitudes varied significantly with regard to the demographic characteristics of respondents. Logistic regression analysis showed that gender and age were the influential predictors of favourable versus non-favourable attitudes towards the role of pharmacist.Conclusions: The use of community pharmacies in Iraq was characterized by frequent visits to purchase medicines. Selection of the pharmacy primarily depended on its location. Overall, an under-appreciation of the professional performance of pharmacists was predominant. Raising public awareness towards the important role of community pharmacists in providing public health is warranted.